2019
DOI: 10.19277/bbr.16.1.196
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to the Mediterranean diet in Portuguese university students

Abstract: Mediterranean diet (MedDiet) is one of the most recognized healthy dietary patterns. Despite the beneficial effects of healthy eating habits on academic performance, university students make unhealthy food choices. Crosssectional information regarding MedDiet adherence was collected in 305 students from the Universidade Lusófona de Humanidades e Tecnologias, from different academic courses, related or not with health sciences. To assess the MedDiet adherence, the participants completed a validated 14-point que… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
5
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 36 publications
3
5
1
1
Order By: Relevance
“…In a study carried out on college students in Portugal, 59% of them showed average adherence, between 6 and 9 points presenting only 12.5% high adherence [46]. Although these results are low for a mediterranean country they are far from the results of this study.…”
Section: Discussioncontrasting
confidence: 78%
See 1 more Smart Citation
“…In a study carried out on college students in Portugal, 59% of them showed average adherence, between 6 and 9 points presenting only 12.5% high adherence [46]. Although these results are low for a mediterranean country they are far from the results of this study.…”
Section: Discussioncontrasting
confidence: 78%
“…According to our research, a study carried out in Colombia found that female sex was significantly higher in terms of a very low-quality diet and with a greater inclination for processed foods, unlike men [46]. The only statistically significant correlation for adherence to MD was the one estimated for eating behaviors.…”
Section: Discussionmentioning
confidence: 55%
“…We found evidence of both positive and negative features in the MED populations taking part in this study. On the favorable side, and in good agreement with earlier studies also conducted in the general adult population from SP [ 15 , 16 , 28 , 30 , 37 , 42 ], PT [ 44 , 45 ], IT [ 17 ], or GR [ 19 ], our results supported a clear preference for OO against butter, with OO displaying more than 90% of subjects within the MD recommendations, and between ≈60% and 95% consuming less than one portion of butter or cream per day. Nonetheless, the target quantity for OO (≥4 tbsp/day) was reached by ≤30% of the participants.…”
Section: Discussionsupporting
confidence: 91%
“…Regarding the MED participant countries, analogous results with scores in the midrange of the scale were previously reported in SP [ 15 , 16 , 28 , 30 , 37 , 42 , 43 ], PT [ 22 , 44 , 45 ], IT [ 17 , 18 , 46 , 47 , 48 , 49 ], GR [ 50 , 51 ], and CY [ 52 ]. Other Southern European as well as some non-European MED countries [ 23 , 27 , 53 ] have also been attributed a moderate value of MD adherence.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation